2007
DOI: 10.1128/jb.00722-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Gene Cluster Encoding Longus, a Type IV Pilus of Enterotoxigenic Escherichia coli

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains produce a type IV pilus named Longus. We identified a 16-gene cluster involved in the biosynthesis of Longus that has 57 to 95% identity at the protein level to CFA/III, another type IV pilus of ETEC. Alleles of the Longus structural subunit gene lngA demonstrate a diversity of 12 to 19% at the protein level with strong positive selection for point replacements and horizontal transfer.Enterotoxigenic Escherichia coli (ETEC) is an important cause of infant diarrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
1
37
0
3
Order By: Relevance
“…S1). The other proteins encoded on these pilus operons, most of which are involved in pilus assembly, are more highly conserved, both within Longus-expressing strains and between Longus and CFA/III systems (20). Thus, the cof operon can be considered a variant of the lng operon that is transmitted on its own plasmid, an idea supported by phylogenetic analyses of available cofA and lngA sequences (20).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…S1). The other proteins encoded on these pilus operons, most of which are involved in pilus assembly, are more highly conserved, both within Longus-expressing strains and between Longus and CFA/III systems (20). Thus, the cof operon can be considered a variant of the lng operon that is transmitted on its own plasmid, an idea supported by phylogenetic analyses of available cofA and lngA sequences (20).…”
Section: Discussionmentioning
confidence: 72%
“…A PCR-based study of 56 ETEC isolates that employed cofA-and lngA-specific primers identified 38 lngA-positive strains and only two cofA-positive strains (20). We compared published nonredundant LngA amino acid sequences and mapped the nonconserved residues to the LngA homology model ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Strains TW10598 and TW11681 shared the entire ϳ14-kb operon that encodes a type IV pilus known as the longus pilus or CS21 (11,27). Sequences from the longus operon were absent in all plasmid sequences from publicly available ETEC genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, E. coli E1392/75 possesses CS3-and CS1-encoding loci on plasmids pETEC1018 and pETEC746, respectively, whereas pCoo possesses the CS1 cluster, all of which have been described previously (28,57,58). In addition, E. coli E1392/75 pETEC557 also encodes the CFA/III-type IV fimbria (29). To There is limited conservation in the sequences; however, two cysteine residues that are disulfide bonded in dispersin are conserved.…”
mentioning
confidence: 99%